An Exploration of the Methods of Communication between Policy Makers and Providers that Help Facilitate Implementation of Primary Health Care Reforms. Issue 4 (19th May 2019) - Ashcroft, Rachelle; Kennedy, Lauren; Van Katwyk, Trish
ABSTRACT: Policy reforms targeting organizational structure, expansion of interprofessional teams, inclusion of collaborative practices, and shifting provider remuneration models have resulted with substantial change for providers and leaders with primary health care settings in Canada, USA, and elsewhere. Discourse analysis provides a theoretical lens that can help build an understanding about the implications of different modes of communication on the implementation of new policy initiatives like new models of primary health care. This study applies discourse analysis to determine the modes of communication that were used to relay policy expectations underpinning a newly emerging interprofessional model of primary health care. We conducted a secondary analysis of a qualitative study conducted between 2010 and 2011 with primary health care leaders and policy informants during a period of health care reform in Canada. In-depth semi-structured interviews were conducted with seven key policy informants (PIs) and 29 primary health care leaders (physicians, executive directors, and non-physician clinical leaders). Discourse analysis is useful in the investigation of the meanings of health, health policy, and health care settings.